PERAN PEMERINTAH DAERAH DALAM PENGEMBANGAN PARIWISATA DI KABUPATEN MERANGIN TAHUN 2018-2020 - Fathonah, Nurul; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Merangin Regency is one of the areas in Jambi Province which is rich in tourism potential. Merangin Regency has many natural tourist attractions. If this tourist attraction is managed and developed well and appropriately, it will become an interesting tourist destination to visit. There are still many tourist attractions that have limitations and problems. Such as a lack of information regarding the existence of tourist attractions and a lack of facilities and infrastructure. This research was conducted to find out the role of the Regional Government in tourism development as a regulator, facilitator and dynamist and what are the obstacles in developing tourism in Merangin Regency. This research was conducted using a qualitative research approach with descriptive research type. With data collection techniques through interviews and documentation. The results of this research show that the role of Regional Government in tourism development includes: 1) The role of the Government as a Regulator by making policies regarding maintenance and carrying out monitoring and evaluation 2) The role of the Government as a Facilitator of government involvement by creating programs and carrying out physical development and also carrying out tourism promotion, 3) The role of the Government as a dynamist by providing training to the community. Obstacles in developing tourism in Merangin Regency are community participation, limited infrastructure, limited funds. Keywords: Role of Regional Government, Tourism Development, Natural Tourism Objects